2013
DOI: 10.1021/ja3087467
|View full text |Cite
|
Sign up to set email alerts
|

On/Off Photoswitching in a Cyanide-Bridged {Fe2Co2} Magnetic Molecular Square

Abstract: A repeatable bidirectional paramagnetic ↔ diamagnetic photomagnetic effect has been observed in the cyanide-bridged Fe–Co square complex {[Fe{B(pz)4}(CN)3]2[Co(bik)2]2}(ClO4)2·3H2O [B(pz)4 = tetrapyrazolylborate, bik = bis(1-methylimidazol-2-yl)ketone]. Magnetic measurements and low-temperature single-crystal X-ray diffraction experiments have shown that a complete electron transfer from the diamagnetic FeII −Co III state to the paramagnetic FeIII −Co II metastable state is induced by 808 nm laser light irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
136
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 28 publications
24
136
0
8
Order By: Relevance
“…Nevertheless, the best efficiency for photoexcitation is obtained in the NIR region, in agreement with the position of the MMCT band . Only one study has demonstrated the photoreversibility by following the ET process using magnetic and structural measurements . Figure shows the effect of four successive irradiations of the square 7 , such that a 808 nm excitation at 20 K led to an increase in the χT product, in agreement with the population of the paramagnetic state, whereas a further 532 nm excitation results in the opposite variation of the χT product.…”
Section: Light‐induced Etmentioning
confidence: 54%
See 1 more Smart Citation
“…Nevertheless, the best efficiency for photoexcitation is obtained in the NIR region, in agreement with the position of the MMCT band . Only one study has demonstrated the photoreversibility by following the ET process using magnetic and structural measurements . Figure shows the effect of four successive irradiations of the square 7 , such that a 808 nm excitation at 20 K led to an increase in the χT product, in agreement with the population of the paramagnetic state, whereas a further 532 nm excitation results in the opposite variation of the χT product.…”
Section: Light‐induced Etmentioning
confidence: 54%
“…Plot of χ M T vs. time for the square {[(pzTp)Fe(CN) 3 ] 2 [Co(bik) 2 ] 2 }[ClO 4 ] 2 · 2H 2 O 7 under cycles of successive irradiation at 808 nm (6 mW cm –2 ) and 532 nm (10 mW cm –2 ) at 20 K. Reproduced with permission. From ref …”
Section: Light‐induced Etmentioning
confidence: 99%
“…When the N- donors are the metallo-ligands, [Mo(CN) 8 ] 3− or [Fe(Tp)(CN) 3 ] − (in the cyanide-bridged rhombus molecules of formula {[Mo(CN) 8 ] 2 [Fe( Me bik) 2 ] 2 }( H MeIm) 2 ·5H 2 O·CH 3 CN, where Me ImH + = N-methyl-imidazolium cation, and {[Fe III (Tp)(CN) 3 ] 2 [Fe II ( Me bik) 2 ] 2 }. [Fe III (Tp)(CN) 3 ] 2 ·18H 2 O·4CH 3 OH), the most efficient effect are observed at 405 and 808 nm, respectively (Mondal et al, 2013, 2014) These differences should be related to the different electronic structures of the compounds and the nature of the accessible excited-states involved in the LIESST effect. The occurrence of reverse LIESST effect in some of these compounds was also proposed to account for a partial decrease of the photomagnetic response (Moussa et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…B. Fe 2+ , Co 2+ , Ni 2+ , Pd 2+ und Pt 2+ , und zweizähnige Liganden wie Cyanid, Stickstoff-Heterocyclen, ditopische N-heterocyclische Carbene, Isonitrile und Phosphane. [4] Um die be-eindruckende strukturelle Vielfalt der molekularen Quadrate noch weiter aufzufächern, sind neue Synthesestrategien erforderlich. Hier beschreiben wir zum ersten Mal die Synthese eines molekularen Quadrats unter Verwendung von phosphaorganometallischen Baueinheiten.…”
unclassified
“…Angesichts der bereits zuvor etablierten Fähigkeit von 1,3-Diphosphacyclobutadien-Komplexen zur Koordination von einwertigen Münzmetallionen [8] fokussierten wir uns auf Gold(I)-Verbindungen. Wir berichten nun über die Synthese und die strukturelle Charakterisierung der neuen, achtkernigen Au 4 Co 4 -Verbindung [Au{Co(P 2 C 2 tBu 2 ) 2 }] 4 (1), die aus vier Au + -Kationen und vier [Co(P 2 C 2 tBu 2 ) 2 ] À -Einheiten gebildet wird.…”
unclassified